Body mass index standard deviation score and obesity in children with type 1 diabetes in the Nordic countries. HbA1c and other predictors of increasing BMISDS. Issue 7 (31st May 2018) - Birkebaek, NH; Kahlert, J; Bjarnason, R; Drivvoll, AK; Johansen, A; Konradsdottir, E; Pundziute‐Lyckå, A; Samuelsson, U; Skrivarhaug, T; Svensson, J; ,
Abstract : Background: Intensified insulin therapy may increase body weight and cause obesity. This study compared body mass index standard deviation score (BMISDS) and obesity rate in children with type 1 diabetes (T1D) in Denmark, Iceland, Norway and Sweden, and uncovered predictors for increasing BMISDS. Methods: Data registered in the Nordic national childhood diabetes databases during the period 2008‐2012 on children below 15 years with T1D for more than 3 months were compiled, including information on gender, age, diabetes duration, hemoglobin A1c (HbA1c ), insulin dose, severe hypoglycemia (SH), treatment modality, height and weight. The Swedish reference chart for BMI was used for calculating BMISDS. Results: Totally, 11 025 children (48% females) (30 994 registrations) were included. Medians by the last recorded examination were: age, 13.5 years; diabetes duration, 4.3 years; HbA1c, 7.9% (63 mmol/mol); insulin dose, 0.8 IU/kg/d and BMISDS, 0.70. Obesity rate was 18.5%. Adjusted mean BMISDS (BMISDS adj) was inversely related to HbA1c and directly to diabetes duration. Higher BMISDS adj was found in those with an insulin dose above 0.6 IU/kg/d, and in girls above 10 years. Pump users had higher BMISDS adj than pen users, and patients with registered SH had higher BMISDS adj than patients without SH (both P  < .001). Conclusion: Obesity rate in children with T1D in the Nordic countries is high, however, with country differences. Low HbA1c, long diabetes duration, higher insulin dose, pump treatment and experiencing a SH predicted higher BMISDS. Diabetes caregivers should balance the risk of obesity and the benefit of a very low HbA1c.